In search of good energy policy / edited by Marc Ozawa, Jonathan Chaplin, Michael Pollitt, David Reiner, Paul Warde. - Ozawa, Marc; Chaplin, Jonathan; Pollitt, Michael G.; Reiner, David M.; Warde, Paul (Cambridge studies on environment, energy and natural resource governance., 2019)
Drawing on political science, economics, philosophy, theology, social anthropology, history, management studies, law, and other subject areas, In Search of Good Energy Policy brings together leading academics from across the social sciences and humanities to offer an innovative look at why science and technology, and the type of quantification they champion, cannot alone meet the needs of energy policy making in the future. Featuring world-class researchers from the University of Cambridge and other leading universities around the world, this innovative book presents an interdisciplinary dialogue in which scientists and practitioners reach across institutional divides to offer their perspectives on the relevance of multi-disciplinary research for 'real world' application. This work should be read by anyone interested in understanding how multidisciplinary research and collaboration is essential to crafting good energy policy.